British association for sexual health and HIV UK national guideline for the management of infection with Chlamydia trachomatis , 2026 - John Saunders; Nathan Burley; Susie Brice; Luke Cannon; Sarah Cochrane; Alice Milligan; Rachel Pitt-Kendall; Vicki Sellors; Cara Saxon (International Journal of STD & AIDS, 2026)
This guideline provides details on the pathology and clinical features of Chlamydia trachomatis infection and makes recommendations for diagnostic tests, treatment regimens and the health promotion principles needed for the effective management of chlamydia, in people aged 16 years or older attending sexual health services. The guideline is primarily aimed at level 3 sexual health services in the UK, although it could also serve as a reference guide for sexually transmitted infection services at other levels. This guideline is an update of the previous one published in 2015.